Efficient, dopant free phenazine based hole transporting materials for high performance perovskite solar cells. (15th September 2021) - Maddala, Gurulakshmi; Gade, Ramesh; Ahemed, Jakeer; Kalvapalli, Susmitha; Simhachalam, Narendra Babu; Chetti, Prabhakar; Pola, Someshwar; Mitty, Raghavender
Graphical abstract: Highlights: Synthesized Phenazine based HTMs, viz. DPPP, DPPPM, DPPPOMe, DPPPCl and DPPPF. This work emphasizes Phenazine based new multi-chromophore conjugate HTMs. PSCs developed with Ag electrode and efficient Phenazine based new HTMs. DPPPF HTM based devices attained efficiency 18.20% with Jsc 25.80 mA/cm 2 . Abstract: The present work demonstrates, a new type of phenazine core-based hole transporting materials (HTMs) were synthesized and tested for improved power conversion efficiency via enhanced short-circuit density (Jsc ) of 25.80 mA/cm 2, which is much higher as compared with Spiro-OMeTAD benchmark material in perovskite solar cells (PSCs). All the synthesized new phenazine core-based HTMs were thoroughly characterized with various spectroscopic techniques. The strong electron-donating triphenylamine (D) and electron-accepting phenazine (A) units communicate through a pyrene system (π) with large intramolecular charge transfer (ICT) character in these HTMs and hence no requirement of additional dopants or additives throughout the device fabrication process. The framework of the PSCs device, FTO-TiO2 3 NH3 PbI3 ew-HTMs, was assembled through new HTMs such as DPPP, DPPPCl, DPPPF, DPPPM and DPPPOMe and Methylammonium lead iodide (CH3 NH3 PbI3 ) as materials. PSCs with DPPPF and Spiro-OMeTAD HTMs, revealed power conversion efficiency (PCE) of 18.20% and 17.57% with an active area of 3.02 and 2.16 cm 2 respectively. The stability of the devices was examined after 60 days, and found the PCE of 17.48% for DPPPF based device, whereas spiro-OMeTAD based device revealed PCE of 8.34%. Furthermore, the present study demonstrates DPPP series HTMs as possible replacements to the Spiro-OMeTAD, owing to their very simple synthesis process and dopant-free conditions, and their better device performance.